Ring‐selective fragmentation in the tirapazamine molecule upon low‐energy electron attachment - Arthur‐Baidoo, Eugene (2021)
S.D. acknowledges support for Open Access Funding by the Austrian Science Fund as well as the Radiation Biology and Biophysics Doctoral Train-ing Programme (RaBBiT, PD/00193/2012); UIBD/04378/2020 (UCIBIO); and UIBD/00068/2020 (CEFITEC). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.